An Antioxidant Screen Identifies Candidates for Protection of Cochlear Hair Cells from Gentamicin Toxicity - Noack, Volker; Pak, Kwang; Jalota, Rahul; Kurabi, Arwa; Ryan, Allen F. (Frontiers in Cellular Neuroscience, 2017)
Reactive oxygen species are important elements in ototoxic damage to hair cells (HCs), appearing early in the damage process. Higher levels of natural antioxidants are positively correlated with resistance to ototoxins and many studies have shown that exogenous antioxidants can protect HCs from damage. While a very wide variety of antioxidants with different characteristics and intracellular targets exist, most ototoxicity studies have focused upon one or a few well-characterized compounds. Relatively little research has attempted to determine the comparative efficacy of large variety of different antioxidants. This has been in part due to the lack of translation between cell culture and in vivo measures of efficacy. To circumvent this limitation, we used an in vitro assay based on micro-explants from the basal and middle turns of the neonatal mouse organ of Corti to screen a commercial redox library of diverse antioxidant compounds for their ability to protect mammalian HCs from a high dose of the ototoxic antibiotic gentamicin. The library included several antioxidants that have previously been studied as potential treatments for HC damage, as well as many antioxidants that have never been applied to ototoxicity. The micro-explants were treated with 200 μM gentamicin alone, gentamicin plus one of three dosages of a redox compound, the highest dosage of compound alone, or were untreated. HC counts were determined before the gentamicin insult and at 1, 2 and 3 days afterward to evaluate the HC survival. From a total of 81 antioxidant compounds, 13 exhibited significant protection of HCs. These included members of a variety of antioxidant classes with several novel antioxidants, not previously tested on HCs, appearing to alleviate the damaging gentamicin effect. Some compounds previously shown to be protective of HCs were correspondingly protective in this in vitro screen, while others were not. Finally, one of the three pro-oxidant compounds included in the library as well as six antioxidants exhibited evidence of toxicity in the absence of gentamicin. The results demonstrate the wide variability in the ability of antioxidants to protect HCs from high-dose gentamicin damage, and identify promising candidate leads for further study as potential drug targets.